Personnel Potential of Libraries in Music and Art Schools: State and Prospects of Development - N. G. Orlova; M. N. Kolesnikova (Библиосфера)
The article reflects the results of a local study of the human resources of libraries in music and art schools of St. Petersburg, conducted in 2020, assesses the current state of their human resources and suggests possible ways of its development. Libraries in children’s music and art schools (CMS/CAS) are an important participant in the system of additional pre-professional education of children, that’s why the quality of the work of specialists is an important factor in ensuring the quality of the educational process. It was found that the information about these libraries on the websites of the CMS/CAS, is given extremely rare, and it is not structured. Regulatory documents contain very little or no information at all about the tasks of the library, the functional responsibilities of librarians, let along their salaries. The staff is exclusively women; three-quarters of employees are over 50 years old; their work experience in libraries ranges from a minimum to several decades; only the third of employees have a higher library education, more than a half – the pedagogical one, that result in the quality of library activity. Only half of the employees is able to work on computer. Qualification categories to librarians are not assigned. All respondents need advanced training in basic library processes. In the current situation, the main way to develop the activities of the libraries in the CMS/CAS of St. Petersburg is to transform them into information and library centers for the arts similar to those created in school libraries, and to unite them into a network to overcome the disunity of the professional group of librarians of the CMS/CAS.